XVII State Congress Adide Federation: “Equity, Equality and Educational Inspection” - Barea Romero, Cristóbal (Avances en Supervisión Educativa, 2024)
Review of the XVII State Congress Adide Federation, held in Códoba on November 13, 14 and 15, 2024, on the theme of “Equity, Equality and Educational Inspection”.